Effects of Asphalt Mix Design Properties on Pavement Performance: A Mechanistic Approach. (2nd August 2016) - Abu Abdo, Ahmad M.; Jung, S. J.
Abstract : The main objective of this study was to investigate the effects of hot mix asphalt material properties on the performance of flexible pavements via mechanistic approach. 3D Move Analysis software was utilized to determine rutting and cracking distresses in an asphalt concrete (AC) layer. Fourteen different Superpave mixes were evaluated by utilizing results of the Dynamic Modulus (| E ⁎ | ) Test and the Dynamic Shear Modulus (| G ⁎ | ) Test. Results showed that with the increase of binder content, the tendency of rutting in AC layer increased. However, with the increase of binder content, the cracking of AC layer lessened. Furthermore, when different binder grades were evaluated, results showed that with the increase of the upper binder grade number, rutting decreased, and with the increase of the lower binder grade number, rutting increased. Furthermore, analysis showed that with the increase of the lower binder grade number, higher percent of bottom up cracks would result. As a result of the analysis, binder grade should not be solely considered for cracking in AC layer; binder content and aggregate structure play a big role. Finally, results illustrated that the mechanistic approach is a better tool to determine the performance of asphalt pavement than commonly used methods.